Is There a Metropolitan Bias? The Relationship between Poverty and City Size in a Selection of Developing Countries - Ferre, Celine; Ferreira, Francisco H.G.; Lanjouw, Peter (Oxford University Press on behalf of the World Bank, 2014)
This paper provides evidence from eight developing countries of an inverse relationship between poverty and city size. Poverty is both more widespread and deeper in very small and small towns than in large or very large cities. This basic pattern is generally robust to the choice of poverty line. The paper shows, further, that for all eight countries, a majority of the urban poor live in medium, small or very small towns. Moreover, it is shown that the greater incidence and severity of consumption poverty in smaller towns is generally compounded by similarly greater deprivation in terms of access to basic infrastructure services, such as electricity, heating gas, sewerage and solid waste disposal. We illustrate for one country – Morocco – that inequality within large cities is not driven by a severe dichotomy between slum dwellers and others. Robustness checks are performed to assess whether the findings in the paper hinge on a specific definition of “urban area”; are driven by differences in the cost of living across city-size categories; by reliance on an income-based concept of well-being; or by the application of small-area estimation techniques for estimating poverty rates at the town and city level.